Program Fisioterapi melalui Otago Exercise dan Skrining Kekuatan Otot Tungkai Lansia di Yayasan Amal Bakti Abdie Huffadz Kota Makassar - Ita Rini; Nurhikmawaty Hasbiah; Meutiah Mutmainnah Abdullah; Andi Bessse Ahsaniyah A. Hafid; Yery Mustari; Andi Rizky Arbaim Hasyar; Djohan Aras; Hamisah Hamisah; Marseila Abigael Pasorong; Ivory Princessa Feodora Liklikwatil; Yuyun Syahira; Zein Mauludil Adhim; Ferdian Rafi Rahmad (Jurnal Abdimas Kesehatan (JAK), 2026)
The number of older adults in Indonesia, particularly in Makassar City, has led to a growing demand for preventive, promotive, curative, and rehabilitative health services. Older adults are vulnerable to declines in lower-limb muscle strength, balance, and an increased risk of falls, all of which affect their quality of life. This community service program was designed to provide comprehensive management through education, functional screening, and physiotherapy interventions in the form of elderly exercise programs and Otago Exercise balance training. Elderly exercise has been shown to reduce depression, improve sleep quality, enhance respiratory function, and strengthen social interaction. Meanwhile, the Otago Exercise focuses on improving lower-limb muscle strength, enhancing both static and dynamic balance, and preventing falls. Muscle strength screening was conducted using the Two Minute Step Test. The program’s implementation demonstrated improvements in physical fitness, balance, and independence in daily activities among older adults. With a structured functional physiotherapy approach, this program is expected to provide a sustainable solution for improving the physical, psychological, social, and cognitive health of the elderly.